Effect of the T6 heat treatment on corrosion behavior of additive manufactured and gravity cast AlSi10Mg alloy. Issue 10 (8th April 2019) - Girelli, Luca; Tocci, Marialaura; Conte, Manuela; Giovanardi, Roberto; Veronesi, Paolo; Gelfi, Marcello; Pola, Annalisa
Abstract: This study investigates the corrosion behavior of AlSi10Mg alloy produced by additive manufacturing and gravity casting before and after T6 heat treatment. Electrochemical tests showed that the additive manufactured material in as‐produced condition exhibits high corrosion resistance, due to the very fine microstructure, while immersion test allowed to identify an exfoliation‐like corrosion phenomenon, which caused a significant mass loss. In this case, T6 heat treatment was beneficial for corrosion resistance since the related change in microstructure led to a less detrimental corrosion mechanism. Therefore, the T6 heat treatment resulted necessary to use additive manufactured AlSi10Mg components in aggressive chloride‐bearing environments. Abstract : Immersion corrosion tests on samples with sharp edges of AlSi10Mg alloy produced by additive manufacturing allowed indentifying a deleterious corrosion mechanism in as‐built condition. Electrochemical tests were not adequate to reveal this behavior. Due to the microstructural evolution after T6 heat treatment, samples exhibited a lower mass loss in heat‐treated conditions than in as‐built condition.